Language enrichment activities for preparatory English / Ho Chui Chui - Ho, Chui Chui (Universiti Teknologi MARA Kedah, Sungai Petani, 2002)
This article deals with the use of language enrichment activities for students taking the Preparatory English course in Universiti Teknotogi MARA. The author shares her ideas to make the teaching and learning of fft/s course a more pleasant and appealing process.